Corvi, Rationalized Housing Typologies: An Exercise in Standardization - Alvarez-Campos, D (UNIV BIO-BIO, 2021)
The social housing designed by the teams of the Corporacion de la Vivienda (CORVI) constitutes a material presence of enormous influence within Chilean society and within the community of architectural practices. This paper observes the work of these teams, by analyzing the information contained in the CORVI document called "Tipologias de viviendas racionalizadas 1966-1972 (Rationalized Housing Typologies 1966-1972)", which provides data on the shapes, dimensions, materials, and programs of eighteen housing typologies developed by the design teams between 1966 and 1971. Not all of these prototypes were built, but as a whole, it shows how the idea of social housing rationalization was conceived, and how it became an exercise in standardization, based on typologies, from which it is possible to learn both the forms of order and layout of everyday life that they propose, along with the interpretative flexibility used in their communication.